Statement Regarding the Situation of the Catholic Times - The English Speaking Catholic Council (ESCC) (2010)

November 2010 : Anniversary Newspaper - Literacy Volunteers of Quebec (2010)
Number of pages: 22

Youth Employment Services Celebrates 35,000 Served, 15 Years Strong - Youth Employment Services (YES) (2010)

Strategic Plan : 2011-2016 - The English Speaking Catholic Council (ESCC) (2010)

Coasters Association Inc. Presentation to the Standing Senate Committee on Official Languages - Coasters Association (2010)
The Lower North Shore, with a total population of less than six thousand, consists of fourteen (14) isolated communities, twelve predominantly English speaking, two Francophone communities, and two Montagnais reserves (Five municipalities.) These communities are spread over 550 km on the North East coast of Quebec.
Keywords: Official Language Minority Community (OLMC)

Presentation to the Standing Senate Committee on Official Languages - Gignac, Jean-Sébastien (2010)

A Consultation - Quebec Federation of Home and School Associations (QFHSA) (2010)
The Quebec Federation of Home and School Associations Inc. welcomes the opportunity to present this consultation brief to the Standing Senate Committee on Official Languages.
Keywords: Official Language Minority Community (OLMC)

Diverse Expressions : A Collection Of Poems - The Women Of Les Maisons Transitionnelles O3 (2010)
Number of pages: 27

Community Health Education Program (CHEP) : 2009-2010 - Community Health and Social Services Network (CHSSN); McGill University Health Centre (2010)
The Community Health Education Program (CHEP) is a dynamic program that facilitates distance community learning of health and social information for English-speaking Quebecers in remote communities, via five different components: videoconferencing, telephone conferencing, videoconferencing Session DVD’s, community radio (Internet access), follow-up activities (face-to-face)

The Twenty-Ninth Annual Report - The English Speaking Catholic Council (ESCC) (English Speaking Catholic Council, 2010)

Annual General Meeting : Book of Reports - Quebec Federation of Home and School Associations (QFHSA) (2010)
Parallel title: Building Our Future... Together!

Annual Report : 2009-2010 - 4Korners (2010)

2009-10 Annual Report - Leading English Education and Resource Network (LEARN) (2010)
In a province as vast as Quebec, and with schools and school boards scattered over an enormous geographic expanse, the notion of bringing people together to create a COMMUNITY of collaboration may appear daunting, if not impossible. In reality, when people share similar interests and common goals, those physical impediments can quickly disappear. This is especially true when the ultimate objective is the academic success of our children in elementary and high schools. LEARN’s focus is to serve as a catalyst and facilitator for the creation of communities of collaboration composed of educators, parents and students across the province. It is our organization’s objective to make every effort possible to get the well-intentioned forces within the English educational milieu together to share the wealth of knowledge and experience that resides there.

Perspectives on Education : Voices of Eminent Canadians - Leading English Education and Resource Network (LEARN) (2010)
Number of pages: 176

Poetry and Education : Possibilities and Practices - Leading English Education and Resource Network (LEARN) (2010)
Number of pages: 318

Rapport Annuel 2009-2010 - Leading English Education and Resource Network (LEARN) (2010)
Dans une province aussi vaste que le Québec, où les écoles et les commissions scolaires sont dispersées sur une immense étendue géographique, la notion de rassembler les gens pour en faire une COMMUNAUTÉ de collaboration semble un obstacle gigantesque, sinon insurmontable. Dans la réalité, les gens partagent des intérêts similaires et des objectifs communs et cette notion d’impossibilité physique s’estompe rapidement. Cette évolution est particulièrement vraie quand l’objectif ultime est la réussite scolaire de nos enfants au niveau des écoles élémentaires et secondaires. LEARN a pour objectif de servir de catalyseur et de facilitateur pour la création de communautés de collaboration réunissant les éducateurs, les parents et les élèves à l’échelle de la province. L’objectif de notre organisation est de déployer tous les efforts possibles pour réunir les forces positives du milieu éducatif anglophone afi n de contribuer au partage des connaissances et des expériences disponibles au sein de notre communauté.

[Annual Report 2009-2010] - NDG Community Council (NDGCC) (2010)

[Annual Report 2009-2010] - NDG Community Council (NDGCC) (2010)

Annual Report / Rapport annuel 2009-2010 - Quebec Community Groups Network (QCGN) (2010)

The Sheila & Victor Goldbloom Distinguished Community Service Award - Quebec Community Groups Network (QCGN) (2010)
Keywords: Official Language Minority Community (OLMC)

Annual Report 2009-2010 - Voice of English-speaking Quebec (VEQ) (2010)